Molecular analysis of the parallel domestication of the common bean (Phaseolus vulgaris) in Mesoamerica and the Andes. Issue 1 (5th November 2012) - Bitocchi, Elena; Bellucci, Elisa; Giardini, Alessandro; Rau, Domenico; Rodriguez, Monica; Biagetti, Eleonora; Santilocchi, Rodolfo; Spagnoletti Zeuli, Pierluigi; Gioia, Tania; Logozzo, Giuseppina; Attene, Giovanna; Nanni, Laura; et al.
Summary We have studied the nucleotide diversity of common bean, Phaseolus vulgaris, which is characterized by two independent domestications in two geographically distinct areas: Mesoamerica and the Andes. This provides an important model, as domestication can be studied as a replicate experiment. We used nucleotide data from five gene fragments characterized by large introns to analyse 214 accessions (102 wild and 112 domesticated). The wild accessions represent a cross‐section of the entire geographical distribution of P. vulgaris. A reduction in genetic diversity in both of these gene pools was found, which was three‐fold greater in Mesoamerica compared with the Andes. This appears to be a result of a bottleneck that occurred before domestication in the Andes, which strongly impoverished this wild germplasm, leading to the minor effect of the subsequent domestication bottleneck (i.e. sequential bottleneck). These findings show the importance of considering the evolutionary history of crop species as a major factor that influences their current level and structure of genetic diversity. Furthermore, these data highlight a single domestication event within each gene pool. Although the findings should be interpreted with caution, this evidence indicates the Oaxaca valley in Mesoamerica, and southern Bolivia and northern Argentina in South America, as the origins of common bean domestication.